2017
DOI: 10.1093/mnras/stx1891
|View full text |Cite
|
Sign up to set email alerts
|

A statistical spectropolarimetric study of Herbig Ae/Be stars

Abstract: We present Hα linear spectropolarimetry of a large sample of Herbig Ae/Be stars. Together with newly obtained data for 17 objects, the sample contains 56 objects, the largest such sample to date. A change in linear polarization across the Hα line is detected in 42 (75 %) objects, which confirms the previous finding that the circumstellar environment around these stars on small spatial scales has an asymmetric structure, which is typically identified with a disk. A second outcome of this research is that we con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 45 publications
(65 reference statements)
5
34
0
Order By: Relevance
“…The data is shown in Table 5. We note that Ababakr et al (2017) also observed a disc in this object through spectropolarimetry, inclined at 146 deg. However, in the interest of consistency with the previous measurement, we use the disc inclination of 80 deg from Navarete et al (2015).…”
Section: Alignment With Discssupporting
confidence: 57%
“…The data is shown in Table 5. We note that Ababakr et al (2017) also observed a disc in this object through spectropolarimetry, inclined at 146 deg. However, in the interest of consistency with the previous measurement, we use the disc inclination of 80 deg from Navarete et al (2015).…”
Section: Alignment With Discssupporting
confidence: 57%
“…Based on the break in accretion rates, we can move this boundary to a critical mass of 4M , remarkably close, but not perfectly so, to the boundary of around B7/8 put forward by Ababakr et al (2017). It is thus implied that there is a transition from magnetically controlled accretion in lowmass HAeBes to another accretion mechanism in high-mass HAeBes at around 4 M .…”
Section: On the Use Of Line Emission As Accretion Rate Diagnosticsupporting
confidence: 54%
“…In contrast, the very different effects observed towards the Herbig Be stars were more consistent with disks reaching onto the central star -hinting at a different accretion mechanism in those. The large sample by Ababakr et al (2017) allowed them to identify the transition region to be around spectral type B7/8.…”
Section: Discussionmentioning
confidence: 99%
“…The latter have emission-line spectra with numerous forbidden emission lines from [Fe II] and [O I] alike the B[e]SGs, and the stars are surrounded by significant amounts of circumstellar dust within their massive accretion disks causing considerable IR excess emission, just as the B[e]SGs. Hence, it is not surprising that confusion exists about the proper classification for a number of objects within this luminosity domain of 4.0 < log L/L < 4.5, and that Galactic B[e]SG candidates also appear as candidates in catalogs of HAeBe stars (see, e.g., [160]). In the absence of clear indications for infall of material, which is a typical characteristic of pre-main sequence stars, alternative discriminators for the classification of such objects are needed.…”
Section: Galactic Objectsmentioning
confidence: 99%